“The Only Way Out Is In”: Transcending Modernity and Embracing Interconnectedness in Gary Snyder and Kenneth White - Kocot, Monika (Text Matters: A Journal of Literature, Theory and Culture, 2022)
It seems that in order to overcome the current ecological crisis we need a new (global?) narrative. If the narrative of “progress” that has functioned as one of the Western cultural myths is linked to the notions of modernity and Enlightenment, then perhaps we need a new vision of modernity and “enlightenment.” This change might become part of a paradigm shift associated with a new view of ecology and the natural world, as proposed by Thich Nhat Hanh, the father of engaged Buddhism in the West. This paper aims to show how Gary Snyder and Kenneth White, two like-minded world-renowned poets and environmental activists, contribute to a new cultural paradigm: transmodernity. The non-dualism and Eastern philosophy that White and Snyder find valuable represent a rejection of Western modernity, and its cult of progress and telos. The emphasis will be placed on the importance of the Hua-Yen Buddhist philosophy, centred upon the metaphor of “Indra’s net,” and the ways in which it informs Snyder’s and White’s writing and Earth-centred activism. Snyder’s Buddhist anarchism is nowadays, more than ever before, intertwined with deep ecology. White’s radical geopoetics is becoming more and more popular, showing that the paradigm is shifting. As I will argue, the impact of “Indra’s net” on the dynamics of this gradual process is undeniable.